Identification of marine debris at Avicennia mangrove root in Pangandaran Beach, West Java - Chotimah, Liana Chusnul; MS, Yuniarti; Andriani, Yuli; Faizal, Ibnu; Prasetiawan, Nanda Radhitia (Acta Aquatica: Aquatic Sciences Journal, 2023)
This research was carried out in Pangandaran Regency, specifically in the Batukaras, Nusawiru, and Bojongsalawe areas, in March-April 2022. This research to determine the characteristics of Avicennia type mangroves, habitat characteristics, and the ability of Avicennia type mangrove roots to trap debris. The method used is the Line Transect (LT) method. The results obtained from research on the characteristics of this type of Avicennia mangrove include that the circumference of mangrove roots ranges from 2-24 cm, the height of mangrove roots ranges from 3-83 cm, and the number of mangrove roots ranges from 925-2988 roots. The wider the area, the more debris you will find. Based on the results of the calculation of the characteristics of the Avicennia-type mangrove habitat in Pangandaran, it is in a good range. The calculations include salinity in the range of 15-22 ppt, a temperature of 32-34 °C, a pH value of 7,6-8, and DO (dissolved oxygen) of 4-4,5 mg/L. The trapping of waste in the Avicennia root area is categorized as strong. So the denser the mangrove roots are, the density of debris will increase. This is proven by the large amount of debris found in Batukaras.Keywords: Avicennia mangrove; Characteristics, Category, Density, Marine debris; Type.